Sexualidade no contexto da paraplegia: um estudo das representações sociais - Costa Filho, José Andrade (2017)
Starting from the premise that sexuality always acquired several connotations, in accordance with the meanings and senses that have been and are assigned by the culture, the term sexuality now relates to sexual activity (Biological) now the gender role, influencing the way of being of individuals. Sexuality is constructed from the set of social institutions, cultural, historical and discursive mediated by the device of knowledge-power, since the relationship of power raises standards, control and vigil over at that time is considered okay and normal. The body and sexuality WINS sense why there are in society and are manufactured by them, where the speeches are responsible for regulating and standardizing the sexual behaviours in particular time and context. The disabled body always was seen as negative at all during the story, does not meet the minimum requirements for social cooperation and for the activities required to work in this sense historical determinations, economic, social and cultural rights, outside the context of paraplegia, because the same is characterized as a type of disability that affects motor functions and loss of sensation in the legs. With regard to sexuality, desire in paraplegic person can suffer changes mainly due to psychological and social issues, not denying the existence of organic problems. In this sense, this thesis aims to seize the general social representations of people with paraplegia about your sexuality. It is a field of study multimétodo character backed by the theory of social representations, with locus a public clinic, partnership with the SUS, offices of private clinics and health centers all entered in the city of Campina Grande. For access to participants, there was a Snowball methodology. The sample was composed of 60 participants, these 40 were people diagnosed with paraplegia and 20 health professionals, of both sex (male = 35; Female = 25) between 22 and 57 years. As an instrument of a questionnaire were used Biossociodemografico collection, free association of Words (TALP) and a semi-structured interview, the data from the first instrument were processed by the Software SPSS 19.0 and analyzed by descriptive statistics; the narratives from the interviews of the participants with paraplegia were triggered by Alceste software and analyzed by hierarchical classification descente (CHD),the professionals were processed by Iramutec software and evaluated for CHD, plus the analysis of similarity; the words coming from the TALP were processed by the Tri-deux-mots and analyzed by factor analysis. The results point in relation to the profile of the paraplegic people an average of age of 31.78 years (SD = 8, 63), male predominance (70%), education (50%) attended elementary school, 37.5% and 12.5 higher education, marital status, single (77%); 80% present as cause paraplegia gained, with greater cause auto accidents (55%) and as main neurological lumbar level (65%). The profile of health professionals female predominance (65%); time of 11-15 formed between years (45%) physiotherapists and psychologists (35% respectively) and you don't talk about sexuality with your patients (70%). The social representations of people with paraplegia about your sexuality are related to notorious re-meaning the same, sex and sexuality, the latter as a broader concept, which involves the relationship between two people, attraction, love, pleasure and sexual involvement, where sex is not related only to the genital pleasure, also linked to attraction, desire, the female and the male in order to find love. In this sense the sexuality refers to a person as a whole, their thoughts, feelings, attitudes and behaviours with respect to themselves and to others, while taking into consideration the historicity of each, because this subjective understanding of sexuality relates to experience emotional and could not fail to be mediated by society, where people with paraplegia depends on the process of socialization , experimentation, clarification and information about living your sexuality. Health workers contained their representations about the sexuality related also to a broader sense however characterized the physiological aspect with determinant of same. It is concluded that this thesis may contribute to better quality of life and better inclusion in the social environment in which it is inserted, abolishing the bias, showing that people with paraplegia are able to share the rights and social duties and enjoying a sexuality.